Evaluation of different bacterial honey isolates as probiotics and their efficient roles in cholesterol reduction - Noura O. Abdelsamad; Mona A. Esawy; Zeinab E. Mahmoud; Asmaa I. El-Shazly; Tarek R. Elsayed; Amira A. Gamal (World Journal of Microbiology and Biotechnology, 2022)
Continue to hypothesize that honey is a storehouse of beneficial bacteria, and the majority of these isolates are levansucrase producers. Accordingly, ten bacterial strains were isolated from different honey sources. Four honey isolates that had the highest levansucrase production and levan yield were identified by the partial sequencing of the 16S rRNA gene as Achromobacter sp. (10A), Bacillus paralicheniformis (2M), Bacillus subtilis (9A), and Bacillus paranthracis (13M). The cytotoxicity of the selected isolates showed negative blood hemolysis. Also, they are sensitive to the tested antibiotics (Amoxicillin + Flucloxacillin, Ampicillin, Gentamicin, Benzathine benzylpenicillin, Epicephin, Vancomycin, Amikacin, and Zinol). The isolates had strong alkaline stability (pHs 9, 11) and were resistant to severe acidic conditions (29–100 percent). The tested isolates recorded complete tolerance to both H 2 O 2 and the bile salt (0.3% Oxgall powder) after 24 h incubation. The cell-free supernatant of the examined strains had antifungal activities against C. Albicans with varying degrees. Also, isolates 2M and 13M showed strong activities against S. aureus . The isolates showed strong adhesion and auto-aggregation capacity. Isolate 10A showed the highest antioxidant activity (91.45%) followed by 2M (47.37%). The isolates recorded different catalase and protease activity. All isolates produced cholesterol oxidase and lipase with different levels. Besides, the four isolates reduced LDL (low-density lipoprotein) to different significant values. The cholesterol-reducing ability varied not only for strains but also for the time of incubation. The previous results recommended these isolates be used safely in solving the LDL problem.